2012
DOI: 10.1002/ece3.365
|View full text |Cite
|
Sign up to set email alerts
|

Extensive introgressive hybridization within the northern oriole group (Genus Icterus) revealed by three‐species isolation with migration analysis

Abstract: Until recently, studies of divergence and gene flow among closely-related taxa were generally limited to pairs of sister taxa. However, organisms frequently exchange genes with other non-sister taxa. The “northern oriole” group within genus Icterus exemplifies this problem. This group involves the extensively studied hybrid zone between Baltimore oriole (Icterus galbula) and Bullock's oriole (I. bullockii), an alleged hybrid zone between I. bullockii and black-backed oriole (I. abeillei), and likely mtDNA intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 92 publications
1
19
1
Order By: Relevance
“…This approach may limit the applicability of the IM method for providing realistic estimates of introgression and demographic parameters. However, no severe bias has been observed in other comparable studies (Chan et al., ; Jacobsen & Omland, ; Won & Hey, ), so possible bias in our findings is believed to be minor and have little impact on our main conclusions.…”
Section: Discussioncontrasting
confidence: 45%
“…This approach may limit the applicability of the IM method for providing realistic estimates of introgression and demographic parameters. However, no severe bias has been observed in other comparable studies (Chan et al., ; Jacobsen & Omland, ; Won & Hey, ), so possible bias in our findings is believed to be minor and have little impact on our main conclusions.…”
Section: Discussioncontrasting
confidence: 45%
“…The amount of variation explained at the among-species level in the AMOVA for TGFB2 is 5.1%, indicating that a small portion of the genetic variation can be explained by species boundaries. If the mtDNA paraphyly first described by Baker et al (2003) was the result of a recent mitochondrial introgression between two well-diverged lineages, we would expect to find a great deal of divergence between the nuDNA loci that would not be reflected in the mtDNA (Jacobsen and Omland 2012). Instead, these two lineages appear to be very early in the process of divergingas evidenced by the lack of structure for the majority of nuclear loci, as well as by the lack of reciprocal monophyly in mtDNA.…”
Section: Discussionmentioning
confidence: 96%
“…New analytical methods based on coalescent theory have revealed that divergence occurs with some level of gene flow more commonly than originally thought [4], [5], but estimating the timing of gene flow events remains difficult [11][13]. Some studies have even tested the likelihood of one divergence scenario over another statistically, allowing conclusions about divergence and speciation to be expressed with an explicit level of confidence [10], [14][16]. To evaluate the frequency of divergence with versus without gene flow, the two scenarios must be tested explicitly in a diverse array of taxa.…”
Section: Introductionmentioning
confidence: 99%
“…New analytical methods also facilitate the investigation of hybridization and introgression between closely related taxa [14], [16], [17]. Until recently, introgression has been evaluated almost exclusively using cline theory to examine allele and haplotype frequency changes across hybrid zones [18][20].…”
Section: Introductionmentioning
confidence: 99%